POTRET PERJUANGAN TOKOH UTAMA DAN NILAI DIDIK DALAM NOVEL GURU DANE KARYA SALAMAN FARIS SERTA RELEVANSINYA DALAM PEMBELAJARAN SASTRA DI MADRASAH ALIYAH - NFN Badrin; NFN Hilmiati (MABASAN, 2014)
The problem in this study was a struggle of the main character in Novel Guru Dane (NGD) by Salman Faris. The objectives of this study are to describe: (1) the structure of the NGD by Salman  Faris, (2) the educational values, (3) and the relevance of the educational values with the teaching material of literature subject at Senior  High School. This research was a descriptive qualitative research. The data collected through documentation and interview. The data analysis applied the theory of structural, theory of semiothics, and theory of learning with the steps of identification, classification, description, interpretation, and explanation. The conclusions of this research are  (1) NGD consist of some mutual completing elements, namely theme, characterizations, setting, message, and plot. (2) the effort of the main character to arouse the degnity of the people of Sasak by supporting plurality, humanity, and identity was divided into (a) building cognitive awareness about humanity, (b) building social awareness, (c) breaking down arrogance and the greatness of mistycal things, (d) implanting class awareness, and (e) implanting knighthood/noble actions to the people of sasak; (3) The educational values in the NGD are (a) willingness to sacrifice and to be responsible, (b) respect to the rights and obligations of each other, (c) stickiness to principles and defensiveness to trial, (d) religiousness, (e) patience and lovingness, (f) honesty, (g) hardwork, (h) cooperation, (i) didiscipline; (4) The values in the NGD are in line with those in the standard of content, the standard of competence, and the basic competence of literature  teaching. It also give understanding on the values applications as guidences of behaving, and fit the reality in society which make it relevant to be an object of literature teaching and learning.